2018
DOI: 10.1016/j.ebiom.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Effects of Emphysema in Never-Smokers with Rheumatoid Arthritis Interstitial Lung Disease

Abstract: AimsAutoimmune conditions such as rheumatoid arthritis-related interstitial lung disease (RA-ILD) have been linked to the existence of emphysema in never-smokers. We aimed to quantify emphysema prevalence in RA-ILD never-smokers and investigate whether combined pulmonary fibrosis and emphysema (CPFE) results in a worsened prognosis independent of baseline disease extent.MethodsRA-ILD patients presenting to the Royal Brompton Hospital (n = 90) and Asan Medical Center (n = 155) had CT's evaluated for a definite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 32 publications
5
59
0
1
Order By: Relevance
“…However, in this study, sputum TNF-α concentrations did not correlate with plasma level [112], but this may reflect the short half-life of free TNF-α in biological fluids and the dilution of biological fluids, as seen in induced sputum and lavage samples [113], which are important considerations when interpreting systemic cytokine levels in disease. Despite the dilution of any cytokine overspill from the lungs into the blood, some studies suggest that systemic inflammation could drive the pathologies of COPD: a study of never-smoking patients with rheumatoid arthritis described some participants as having clear evidence of emphysema on computed tomography scans [114]. The exact mechanism of this observation has not been investigated but is likely to involve a combination of genetic and environmental factors alongside systemic inflammation.…”
Section: Evidence For Overspillmentioning
confidence: 99%
“…However, in this study, sputum TNF-α concentrations did not correlate with plasma level [112], but this may reflect the short half-life of free TNF-α in biological fluids and the dilution of biological fluids, as seen in induced sputum and lavage samples [113], which are important considerations when interpreting systemic cytokine levels in disease. Despite the dilution of any cytokine overspill from the lungs into the blood, some studies suggest that systemic inflammation could drive the pathologies of COPD: a study of never-smoking patients with rheumatoid arthritis described some participants as having clear evidence of emphysema on computed tomography scans [114]. The exact mechanism of this observation has not been investigated but is likely to involve a combination of genetic and environmental factors alongside systemic inflammation.…”
Section: Evidence For Overspillmentioning
confidence: 99%
“…Although Jacob et al observed similar morphologic features on HRCT, findings in pulmonary function tests, and clinical features (poor prognosis) between patients with RAIP who never smoked and those with CPFE, the similarities did not assure the same morphogenesis of “emphysema” in these patients, and this series offered no confirmation of histopathological basis of emphysematous cysts ( Jacob et al, 2018 ). Nevertheless, HRCT can reflect the pathological process of diffuse lung disease, and similar CT features of cysts between smokers and non-smokers may reflect a common morphogenesis.…”
mentioning
confidence: 69%
“…In a recent article in EBioMedicine , among patients with comorbid rheumatoid arthritis and interstitial pneumonia (RAIP), Jacob et al report similar findings of emphysema in high-resolution computed tomography (HRCT) of more than 25% of patients who never smoked and those with RAIP who were smokers ( Jacob et al, 2018 ). In addition, those with RAIP who never smoked also shared the same characteristic features in pulmonary function tests as patients with coexistent interstitial pneumonia and emphysema (combined pulmonary fibrosis and emphysema [CPFE]) who smoked.…”
mentioning
confidence: 92%
“…34 Even more strikingly, In RA-ILD, CPFE has been reported in 27% of nonsmokers. 35 In both cohorts, a subset of patients had typical CPFE PFT profiles, although this effect was less on average than in CPFE in idiopathic ILD, with emphysema often limited in extent in CTD-ILD. Thus, spirometric volumes in isolation are often misleading when the severity of ILD is staged in patients with concurrent emphysema, underlining the importance of integrating CT observations.…”
Section: Rationalizing Patterns Of Functional Impairment In Mddmentioning
confidence: 87%